Peran Yayasan Kehati Dalam Program Prakarsa Lintasanhijau Halimun Salak - Wulansari, Marisca; Fawzi, Indra Lestari (Jurnal Ilmu Kesejahteraan Sosial, 2020)
This study describes a Corporate Social Responsibility (CSR) program conducted by Star Energy Geothermal Salak, Ltd. in collaboration with the KEHATI Foundation in a program entitled Green Coridor Initatives Halimun Salak. This study aims to look at type of CSR governance, the role of the KEHATI in CSR activities as well as opportunities, obstacle and challenges in the Green Coridor Initiaves Halimun Salak. This is a qualitative research with a case study design using purposive sampling techniques. Data mining was carried out with a semi-structured in-depth interview with representatives of the Star Energy Geothermal Salak, Ltd., representatives of the KEHATI Foundation, representatives of the Halimun Salak National Park and representatives of one of the beneficiaries, Jarmaskor. The results of the study found that CSR governance is carried out in two forms, namely collaboratively in the first phase of the program (in 2011-2016) and outsourced through philanthropy in the second phase (2018-2021). In the Green Coridor Initiaves Halimun Salak Program, KEHATI acts as a catalyst in cooperation by balancing the interests of companies and national parks in partnerships, becoming a mediator by connecting companies with local NGOs that are able to carry out technical restoration work, facilitating community collaboration with relevant stakeholders for the sustainability of the program and brokering capacity in increasing the technical capacity of the community and building the financial capacity of local NGOs and community groups. KEHATI supporting factors in this collaboration are KEHATI's experience and reputation while the inhibiting factors in this collaboration are the absence of a multi-stakeholder collaboration platform between the company, KEHATI, and Mount Halimun Salak National Park, the high turnover of KEHATI staff in this program and differences in views regarding project management between company and KEHATI.